UNGKAPAN BAHASA RITUAL MAKAN SARO ETNIK TERNATE - Nurbaya (Titian: Jurnal Ilmu Humaniora, 2022)
Abstract: Food as a cultural identity of an ethnic. Cultural identity is a distinguishing feature between one society and another. The ritual of eating Saro is a traditional food ritual at the traditional wedding ceremony of Ternate, North Maluku. This article examines the ritual language of eating Saro in the context of a traditional Ternate wedding from a literary and ethnographic perspective. This article describes the form and style of using the ritual language of eating Saro, which is encoded in certain cultural messages. The method used in this research is descriptive qualitative with ethnolinguistic approach. The results of this study reveal that the expression of the ritual language of eating Saro is in the form of a welcome expression in which there are proverbs, proverbs, and metaphors. In addition, material symbols were found in the ritual of eating Saro. The form of language expression is generally solemn, poetic, and conveyed using figurative language. Keywords: Saro eating ritual, Ternate, Traditional Wedding